2015
DOI: 10.1002/eco.1639
|View full text |Cite
|
Sign up to set email alerts
|

Burn severity alters peatland moss water availability: implications for post‐fire recovery

Abstract: Wildfire is the largest disturbance affecting northern peatlands; however, little is known about how burn severity (organic soil depth of burn) alters post-fire hydrological conditions that control the recovery of keystone peatland mosses (i.e. Sphagnum). For this reason, we assessed the impact of burn severity on moss water availability by measuring soil tension (Ψ ) and surface volumetric moisture content (θ) in burned and unburned portions of a peatland complex 2 years after fire. We found that both high an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 52 publications
(90 reference statements)
1
38
0
Order By: Relevance
“…The conditions of burn severity (complete above‐ground mortality) and depth of burn inherent in this work are also likely an important control on short‐term recovery dynamics (Lukenbach, Devito, Kettridge, Petrone, & Waddington, ). Kettridge et al () show the importance of burn severity on post‐fire ET rates at the plot scale, where high burn severity totally burns through a protective capping layer in feather moss environments.…”
Section: Discussionmentioning
confidence: 99%
“…The conditions of burn severity (complete above‐ground mortality) and depth of burn inherent in this work are also likely an important control on short‐term recovery dynamics (Lukenbach, Devito, Kettridge, Petrone, & Waddington, ). Kettridge et al () show the importance of burn severity on post‐fire ET rates at the plot scale, where high burn severity totally burns through a protective capping layer in feather moss environments.…”
Section: Discussionmentioning
confidence: 99%
“…The dominance of peatland communities varies widely among peatlands driven by differences in climate, hydrogeology (Devito et al, ), age (Benscoter & Vitt, ), disturbance regime (Turetsky et al, ), and recovery period (Benscoter & Vitt, ; Lukenbach et al, ). Sphagnum ‐dominated systems, where increased evaporation may exceed small reductions in tree transpiration postfire (Figure ) (Thompson et al, ), tend to be wetter and deeper peatlands with larger water and carbon stocks available to endure discrete disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Even under high postfire evaporative demand, Sphagnum profiles maintain connectivity with subsurface water stores. In comparison, within the study site, a severe disconnect occurs between the burned feather moss surface and saturated water stores just 0.33 m below (Lukenbach et al, ). This results from (i) the nature of the peat moss structure which, unlike Sphagnum , does not have an effective external wicking system along the moss surfaces (Callaghan et al, ) and (ii) the low moisture content observed at the study site within the near‐surface of the peat (Lukenbach et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our results, we suggest that the degree to which fire effects can be transported laterally via groundwater flow are strongly dependent on postfire hydraulic gradients and soil properties. Given that both the vertical water balance and soil hydraulic properties may be modified by fire (Kettridge et al, , ; Lukenbach et al, ; Semenova et al, ; Sherwood et al, ; Thompson et al, ; Thompson & Waddington, ), this represents a potential postfire feedback which merits further investigation. For example, since deeper organic soils are often less conductive than near‐surface organic soils, burning off the near‐surface soil would lead to a decrease in the average hydraulic conductivity of the organic soil layer (Hinzman et al, ; Neilson et al, ; Quinton et al, ).…”
Section: Discussionmentioning
confidence: 99%